Computational Studies On The Interaction Of Core Histone Tail Domains With Cpg Island - S. PRASANTH KUMAR; RAVI G. KAPOPARA; YOGESH T. JASRAI; RAKESH M. RAWAL (International Journal of Pharma and Bio Sciences, 2012)
It has been elucidated through in vitro studies that core histone tail domains preferentially interact with linker DNA. In the present study, we studied these interactions computationally using molecular docking and isocontour-based electrostatic map approach in order to identify the domains and regions of H3 and H4 tails and DNA contributing for the physical associativeness. We also explored the interaction made by the linker DNA containing methylated CpG dinucleotides (CpG island) with the normal and post-translational modified histone tails. We report that these interactions are electrostatically unfavored if one of the biomolecular partners is methylated thereby, negatively charged zones of DNA and histone tails are required to be absent nearby.